Modified TA-rGO / SiO2 composite filler and rubber composite material

By using modified TA-rGO/SiO2 composite filler, the problem of low wear resistance and strength of shield machine seals is solved, and the mechanical properties and wear resistance of rubber composites are significantly improved, reducing production costs .

CN119410031APending Publication Date: 2025-02-11CHINA RAILWAY ENGINEERING EQUIPMENT GROUP CO LTD
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202411732970.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-29
Publication Date
2025-02-11

AI Technical Summary

Technical Problem

The wear resistance and strength of shield machine seals are low, making it difficult to meet the performance requirements of shield machine.

Method used

Using modified TA-rGO/SiO2 composite filler, the synergistic effect of modified SiO2 and TA covalently modified GO through the silane coupling agent is constructed to achieve uniform dispersion and strengthening of nano-silica and improve rubber composite Mechanical properties and wear resistance of materials.

Benefits of technology

The tensile strength, tear strength and wear resistance of rubber composite materials are significantly improved, production costs are reduced, and rubber performance can be significantly improved with a very small GO content and a small amount of TA-rGO/SiO2 composite filler.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119410031A_ABST
    Figure CN119410031A_ABST
Patent Text Reader

Abstract

The invention provides a modified TA-rGO / SiO2 composite filler and a rubber composite material, belongs to the technical field of rubber sealing materials, and aims to solve the technical problems of poor wear resistance and low strength of a sealing part of a shield tunneling machine. The preparation method of the TA-rGO / SiO2 composite filler comprises the following steps: dispersing and dissolving a silane coupling agent and SiO2 in a solvent I for grafting reaction to obtain silane coupling agent modified SiO2; dispersing and dissolving TA and GO in a solvent II for reduction reaction to obtain TA-rGO; and dispersing the silane coupling agent modified SiO2 and TA-rGO in a solvent III, uniformly stirring, and drying by distillation to obtain the TA-rGO / SiO2 composite filler. A traditional silane coupling agent is used as a bridging agent for grafting modification of silicon dioxide, TA is used for covalent modification of GO, a large number of hydrogen bond binding site platforms are constructed for silicon dioxide loading, self-assembly of the silicon dioxide and the TA is completed through hydrogen bonds, and silicon dioxide can be uniformly dispersed on the surface of GO; the prepared composite filler can be well dispersed in a rubber matrix and can participate in vulcanization of the rubber to generate a strong interface action with the rubber, so that the crosslinking density of the rubber is improved, and the strength and wear resistance of the rubber are improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of rubber sealing materials, and in particular relates to a modified TA-rGO / SiO2 composite filler and a rubber composite material. Background Art

[0002] With the development of the country's urbanization process and the demand for resource exploitation, shield tunneling technology has been widely used in various fields such as urban subways, water conservancy construction, and railway transportation. The main drive system is the direct power of the rotating cutterhead of the shield machine, which can be regarded as the "heart" of the tunneling machine, and the main shaft seal is the protective film of this heart. Therefore, the performance of the shield machine often depends on the performance of the main shaft seal. At present, the main drive seals produced in the domestic market have problems such as weak pressure bearing performance, poor wear resistance, and short service life. In order to solve this problem, it is necessary to modify the traditional sealing materials to produce seals with strong wear resistance, high strength and long service life to ensure the sealing effect of the shield machine.

[0003] Patent Publication No. CN 115181341 A discloses an electrostatically assembled graphene oxide / silicon dioxide natural rubber composite material and its preparation, including natural rubber, rubber additives, and electrostatically assembled graphene oxide / silicon dioxide composite fillers; wherein the electrostatically assembled graphene oxide / silicon dioxide composite fillers are silica modified by silane coupling agent KH550, the surface of silica is connected with amino groups, the amino groups are protonated, and then it is blended with graphene oxide dispersion liquid, and the hydroxyl groups and ammonia cations on the surface of modified silica and the large number of oxygen-containing functional groups on the surface of graphene oxide are hydrogen bonded and electrostatically interacted, thereby obtaining an electrostatically assembled graphene oxide / silicon dioxide composite filler. This patent electrostatically assembles graphene oxide / silicon dioxide to uniformly disperse silicon dioxide on the surface of graphene oxide, improves the dispersibility in natural rubber, and enhances the tensile strength and tear strength of the natural rubber composite material. However, the synergy between graphene oxide / silicon dioxide and other components in rubber is poor, resulting in low improvement in wear resistance and strength of the rubber composite material, making it difficult to maximize the effectiveness of the filler for application in shield machine seals. Summary of the invention

[0004] In order to solve the technical problems of poor wear resistance and low strength of shield machine seals, the present invention proposes a modified TA-rGO / SiO2 composite filler and rubber composite material, which can effectively exert the synergistic effect of GO and SiO2 to achieve a good reinforcement effect to improve the mechanical properties and wear resistance of the material.

[0005] In order to achieve the above object, the technical solution of the present invention is achieved as follows:

[0006] A modified TA-rGO / SiO2 composite filler, the preparation method comprising the following steps:

[0007] Step 1: dispersing and dissolving the silane coupling agent and SiO2 in solvent I for grafting reaction, so that the silanol produced by the hydrolysis of the silane coupling agent reacts with the hydroxyl group on the surface of SiO2 to undergo dehydration reaction and is grafted on the surface of SiO2, centrifuging multiple times (8000-10000rpm, 2-3min) to wash and remove the ungrafted silane coupling agent, and drying in an oven at 60°C for 48h to obtain SiO2 modified with the silane coupling agent;

[0008] Step 2: Disperse and dissolve tannic acid (TA) and graphene (GO) in solvent II for reduction reaction, centrifuge and wash multiple times to remove excess tannic acid, the centrifugal rate is 8000-10000rpm, centrifuge for 10-20min, remove the upper liquid, wash the precipitate with deionized water, and obtain tannic acid-reduced graphene oxide (TA-rGO);

[0009] Step 3: Disperse the silane coupling agent-modified SiO2 and TA-rGO in solvent III, stir magnetically at 25-30°C for 4-5h, and evaporate to dryness to obtain TA-rGO / SiO2 composite filler.

[0010] The silane coupling agent is 3-aminopropyltriethoxysilane (KH-550), 3-(methacryloyloxy)propyltrimethoxysilane (KH-570) or bis-[γ-(triethoxysilyl)propyl]tetrasulfide (Si69).

[0011] The mass ratio of the silane coupling agent to SiO2 is 1:(5-10), and the mass volume ratio of SiO2 to solvent I is 1:(5-10) g / ml.

[0012] The grafting reaction temperature is 25-30° C. and the time is 3-4 hours.

[0013] The solvent I is water / ethanol; the solvent II is water; and the solvent III is water.

[0014] Preferably, the solvent I is water and ethanol in a volume ratio of 1:1.

[0015] The mass ratio of TA to GO is (40-60):1, and the mass volume ratio of GO to solvent II is (10-20):1 mg / ml.

[0016] The temperature of the reduction reaction is 70-90° C. and the time is 8-12 hours.

[0017] The mass ratio of the TA-rGO and the silane coupling agent modified SiO2 is 1: (40-60), and the mass volume ratio of the silane coupling agent modified SiO2 and the solvent III is 1: (5-10) g / ml.

[0018] A rubber composite material, characterized in that it comprises, by weight: 100 parts of nitrile rubber, 50-80 parts of carbon black, 3-6 parts of modified TA-rGO / SiO2 composite filler, 1-2 parts of vulcanizer, 0.8-1.5 parts of accelerator, 4-6 parts of nano zinc oxide, 2-3 parts of stearic acid, and 2-5 parts of antioxidant.

[0019] The vulcanizing agent is sulfur; the accelerator is accelerator DM; and the antioxidant is antioxidant 4010NA.

[0020] A method for preparing a rubber composite material comprises the following steps:

[0021] Step 1: Set the speed of the internal mixer to 80rpm and the temperature to 60℃; add the nitrile rubber to the internal mixer and plasticize for 1-3min, then add carbon black and continue to mix for 1-2min, then add nano zinc oxide, accelerator and antioxidant and continue to mix for 1-2min, then add the above TA-rGO / SiO2 composite filler and continue to mix for 1-2min, then add 2 parts of softener stearic acid and continue to mix for 1-2min; clean for 1min, and debind at 140℃, and dry in an oven at 140℃ for 0.5-1h after debinding to obtain the mixed rubber.

[0022] Step 2: Move the rubber material of step 1 to the open mill for mixing, set the temperature of the front roller to 35-50℃, and the temperature of the rear roller to 30-55℃; slowly add the vulcanizer and accelerator to the open mill for mixing, sweep the wheel plate clean, cut the left and right knives 4-6 times after eating, then thin pass, the roller distance is 0.2-0.5mm, make a triangle package, thin pass 6-8 times, adjust the roller distance to 2-3mm, roll 2-4 times to make a sheet, and place it at room temperature for 8-24 hours to obtain the mixed rubber. Vulcanization temperature is 140-170℃, time is 10min-20min, and pressure is 10-15MPa.

[0023] Beneficial effects of the present invention:

[0024] (1) The present invention uses a silane coupling agent to modify and graft SiO2, and uses TA to covalently modify and reduce GO, so as to construct a large number of hydrogen bond loading platforms for SiO2, which is conducive to better bonding of silica. The two particles are connected by chemical bonds, and nano-silicon dioxide is evenly dispersed on the surface of GO. Therefore, the composite material can be well dispersed in the rubber matrix; in addition, when the silane coupling agent is Si69, the Si69 molecular chain as a bridging agent contains S atoms that can participate in the vulcanization process of the rubber, so that a strong covalent bond is formed between the composite material and the rubber molecular chain, so that the TA-rGO / SiO2 composite filler is cross-linked with the rubber molecule, thereby increasing the cross-linking density. TA is a soluble natural polymer compound, and its molecular structure is rich in a large number of catechol and pyrogallol groups, which give TA a strong interface interaction with the rubber matrix through hydrogen bonds, Π-Π stacking, coordination bonds, etc., and covalent bonds, thereby increasing the cross-linking density again. In addition, tannic acid can also participate in the vulcanization process of (rubber with ZnO activation system). The phenolic hydroxyl group on the surface of tannic acid can complex with ZnO in the rubber system to participate in the vulcanization process, thereby enhancing the interface strength between the composite particles and the rubber matrix. Therefore, TA and silane coupling agent form a dual-driven interface strength, which makes the composite material and the rubber matrix have a stronger interface effect, and can effectively improve the strength and wear resistance of the rubber.

[0025] (2) Silica is grafted and modified by using traditional silane coupling agent as a bridging agent, and TA is covalently modified to construct a large number of hydrogen bonding site platforms for silica loading. The two complete self-assembly through hydrogen bonds, and silica can be evenly dispersed on the surface of GO. The prepared composite filler can be well dispersed in the rubber matrix and can participate in the vulcanization of the rubber to produce a strong interfacial effect with the rubber, thereby increasing the crosslinking density of the rubber and improving the strength and wear resistance of the rubber.

[0026] (3) Compared with the existing process, the composite material with very little GO content (0.06 parts) can produce a good synergistic effect with SiO2 and carbon black; and the TA-rGO / SiO2 composite filler with only 3 parts can greatly improve the mechanical properties and wear resistance of the rubber, which greatly reduces the production cost. BRIEF DESCRIPTION OF THE DRAWINGS

[0027] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.

[0028] Figure 1TEM images of GO and TA-rGO / SiO2, (a, b) are GO at different magnifications; (c, d) are TA-rGO / SiO2 at different magnifications. DETAILED DESCRIPTION

[0029] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0030] Example 1

[0031] A rubber composite material, the preparation method of which is as follows:

[0032] Step 1: Dissolve 3g Si69 in 100ml ethanol-water (1:1) solution and fully hydrolyze it, then add 20g SiO2, stir magnetically at 25℃ for 3h, so that the silanol produced by the hydrolysis of Si69 reacts with the hydroxyl groups on the surface of SiO2 to undergo a dehydration reaction and is grafted onto the surface of SiO2, centrifuge several times (10000rpm, 2min) to wash and remove the ungrafted Si69, dry in an oven at 60℃ for 48h, and set aside;

[0033] Step 2: Add 4gTA to 100ml deionized water, stir magnetically for 30min, then add 1gGO and ultrasonicate for 30min, then react the mixed solution at 90℃ for 8h to obtain TA-rGO suspension. After the reaction is completed, centrifuge and wash several times to remove excess TA. The centrifugal speed is 10000rpm, and the centrifugation is performed for 10min. The upper liquid is removed and the precipitate is washed with deionized water.

[0034] Step 3: Preparation of TA-rGO / SiO2 composite filler: Take 0.4g of TA-rGO and add it into 100ml of deionized water, mix it evenly by ultrasonic for 30min to form a suspension, add the modified SiO2 obtained in step 1 (mass ratio GO:SiO2=1:50) into the suspension, stir it magnetically at 25℃ for 4h, put it into an oven and dry it at 60℃ for 48h to obtain TA-rGO / SiO2 composite filler.

[0035] Step 4: Set the speed of the internal mixer to 80rpm and the temperature to 60℃; add 100 parts of nitrile rubber into the internal mixer and plasticize for 1 minute, then add 50 parts of N550 carbon black and continue to mix for 1 minute, then add 5 parts of nano zinc oxide, 0.5 parts of accelerator DM, and 2 parts of antioxidant 4010NA and continue to mix for 2 minutes, then add the above 3 parts of TA-rGO / SiO2 composite filler and continue to mix for 2 minutes, then add 2 parts of softener stearic acid and continue to mix for 2 minutes; clean for 1 minute, and debind at 140℃, and dry in an oven at 140℃ for 30 minutes after debinding to obtain the mixed rubber.

[0036] Step 5: Move the rubber material of step 4 to an open mixing mill for mixing, set the temperature of the front roller to 50°C, and the temperature of the rear roller to 55°C; add 1 part of sulfur and 0.3 parts of the remaining accelerator back and forth in several times to mix, sweep the wheel plate, cut the left and right kneading knife 5 times after it is clean, then carry out thin pass, the roller spacing is 0.3mm, make triangle bag, thin pass 7 times, adjust the roller spacing to 3mm, roll 4 times to take off the sheet, and place it at room temperature for 12h to obtain the mixed rubber; finally, vulcanize it at a vulcanization temperature of 160°C, a time of 15min, and a pressure of 15MPa to obtain a rubber composite material.

[0037] In order to visually observe the successful composite of GO and SiO2, TEM was used to study the surface morphology of GO and MSGO. Figure 1 As shown in Figures a and b, the TEM morphology of GO with a size of 500 nm and 100 nm, it can be found that GO has a typical lamellar structure with a large area of ​​wrinkled surface. Figures c and d are the TEM morphology of MSGO with a size of 100 nm and 50 nm. It can be found that a large amount of nano-silica is uniformly loaded on the surface of GO, proving that Si69-modified silica is successfully coupled on the surface of GO.

[0038] Comparative Example 1

[0039] The difference from Example 1 is that no TA-rGO / SiO2 composite filler is added, and the following steps are included:

[0040] Step 1: Set the speed of the internal mixer to 80rpm and the temperature to 60℃; add 100 parts of nitrile rubber into the internal mixer and mix for 1 minute, then add 50 parts of N550 carbon black and continue mixing for 1 minute, then add 5 parts of nano zinc oxide, 0.5 parts of accelerator DM, 2 parts of antioxidant 4010NA and continue mixing for 2 minutes, then add 2 parts of softener stearic acid and continue mixing for 2 minutes; clean for 1 minute, and remove the glue at 140℃, and then dry in an oven at 140℃ for 30 minutes to obtain the internal mixer.

[0041] Step 2: Move the rubber material of step 1 to an open mixing mill for mixing, set the temperature of the front roller to 50°C, and the temperature of the rear roller to 55°C; add 1 part of sulfur and 0.3 parts of the remaining accelerator back and forth in several times to mix, sweep the wheel plate, cut the left and right kneading knife 5 times after it is clean, then thin pass, the roller spacing is 0.3mm, make a triangle bag, thin pass 7 times, adjust the roller spacing to 3mm, roll 4 times to get the sheet, and place it at room temperature for 12 hours to obtain the mixed rubber; finally, vulcanize at a vulcanization temperature of 160°C, a time of 15min, and a pressure of 15MPa to obtain a rubber composite material.

[0042] Comparative Example 2

[0043] The difference compared with Example 1 is that only a silane coupling agent is added to modify SiO2, which includes the following steps:

[0044] Step 1: Dissolve 3g Si69 in 100ml ethanol-water (1:1) solution and fully hydrolyze it, then add 20g SiO2, stir magnetically at 25℃ for 3h, so that the silanol produced by the hydrolysis of Si69 reacts with the hydroxyl group on the surface of SiO2 to undergo a dehydration reaction and is grafted onto the surface of SiO2, centrifuge several times (10000rpm, 2min) to wash and remove the ungrafted Si69, and dry in an oven at 60℃ for 48h to obtain the modified SiO2 for use;

[0045] Step 2: Set the speed of the internal mixer to 80rpm and the temperature to 60℃; add 100 parts of nitrile rubber into the internal mixer and mix for 1 minute, then add 60 parts of N550 carbon black and continue mixing for 1 minute, then add 5 parts of nano zinc oxide, 0.5 parts of accelerator DM, and 2 parts of antioxidant 4010NA and continue mixing for 2 minutes, then add the above 3 parts of modified SiO2 composite filler and continue mixing for 1 minute, then add 2 parts of softener stearic acid and continue mixing for 2 minutes; clean for 1 minute, and debind at 140℃, and dry in an oven at 140℃ for 30 minutes after debinding to obtain the mixed rubber.

[0046] Step 3: Move the rubber material of step 1 to an open mill for mixing, set the temperature of the front roller to 50°C, and the temperature of the rear roller to 55°C; add 1 part of sulfur and 0.3 parts of the remaining accelerator back and forth in several times to mix, sweep the wheel plate, cut the left and right kneading knife 5 times after it is clean, then carry out thin pass, the roller spacing is 0.3mm, make a triangle bag, thin pass 7 times, adjust the roller spacing 2-3mm, roll 4 times to take off the sheet, and place it at room temperature for 12 hours to obtain the mixed rubber; finally, vulcanize it at a vulcanization temperature of 160°C, a time of 15min, and a pressure of 15MPa to obtain a rubber composite material.

[0047] Comparative Example 3

[0048] The difference from Example 1 is that the composite filler for reducing GO is not performed using TA, and the method comprises the following steps:

[0049] Step 1: Dissolve 3g Si69 in 100ml ethanol-water (1:1) solution and fully hydrolyze it, then add 20g SiO2, stir magnetically at 25℃ for 3h, so that the silanol produced by the hydrolysis of Si69 reacts with the hydroxyl group on the surface of SiO2 to undergo a dehydration reaction and is grafted onto the surface of SiO2, centrifuge several times (10000rpm, 2min) to wash and remove the ungrafted Si69, and dry in an oven at 60℃ for 48h to obtain the modified SiO2 for use;

[0050] Step 2: Preparation of GO / SiO2 composite filler: Take 1g GO and add it to 100ml deionized water, ultrasonicate for 30min to obtain GO suspension, then add the modified SiO2 obtained in step 1 (mass ratio GO:SiO2=1:50), magnetically stir at 25℃ for 4h, put it in an oven at 60℃ and dry it for 48h to obtain the composite filler.

[0051] Step 4: Set the speed of the internal mixer to 80rpm and the temperature to 60℃; add 100 parts of nitrile rubber into the internal mixer and plasticize for 1 minute, then add 50 parts of N550 carbon black and continue to mix for 1 minute, then add 5 parts of nano zinc oxide, 0.5 parts of accelerator DM, and 2 parts of antioxidant 4010NA and continue to mix for 2 minutes, then add the above 3 parts of composite filler and continue to mix for 2 minutes, then add 2 parts of softener stearic acid and continue to mix for 2 minutes; clean for 1 minute, and debind at 140℃, and dry in an oven at 140℃ for 30 minutes after debinding to obtain the mixed rubber.

[0052] Step 5: Move the rubber material of step 3 to an open mill for mixing, set the temperature of the front roller to 50°C, and the temperature of the rear roller to 55°C; add 1 part of sulfur and 0.3 parts of the remaining accelerator back and forth in several times to mix, sweep the wheel plate, cut the left and right kneading knife 5 times after eating it clean, then carry out thin pass, the roller spacing is 0.3mm, make triangle bag, thin pass 7 times, adjust the roller spacing to 2-3mm, roll 2-4 times to sheet, and place it at room temperature for 12h to obtain the mixed rubber; finally, vulcanize it at a vulcanization temperature of 160°C, a time of 15min, and a pressure of 15MPa to obtain a rubber composite material.

[0053] Comparative Example 4

[0054] The difference compared with Example 1 is that only TA-reduced GO is added as filler, and the following steps are included:

[0055] Step 1: Add 4gTA to 100ml deionized water, stir magnetically for 30min, then add 1gGO and ultrasonicate for 30min, then react the mixed solution at 90℃ for 8h to obtain TA-rGO suspension. After the reaction is completed, centrifuge and wash several times to remove excess TA. The centrifugal speed is 10000rpm, and the centrifugation is performed for 10min. The upper liquid is removed, the precipitate is washed with deionized water, and dried to obtain TA-rGO.

[0056] Step 2: Set the speed of the internal mixer to 80rpm and the temperature to 60℃; add 100 parts of nitrile rubber into the internal mixer and plasticize for 1 minute, then add 50 parts of N550 carbon black and continue to mix for 1 minute, then add 5 parts of nano zinc oxide, 0.5 parts of accelerator DM, and 2 parts of antioxidant 4010NA and continue to mix for 2 minutes, then add the above 0.06 parts of TA-rGO and continue to mix for 2 minutes, then add 2 parts of softener stearic acid and continue to mix for 2 minutes; clean for 1 minute, and debind at 140℃, and dry in an oven at 140℃ for 30 minutes after debinding to obtain the mixed rubber.

[0057] Step three: move the rubber material of step three to an open mixing mill for mixing, set the temperature of the front roller to 50°C, and the temperature of the rear roller to 55°C; add 1 part of sulfur and 0.3 parts of the remaining accelerator back and forth in several times to mix, sweep the wheel plate, cut the left and right kneading knife 5 times after eating it clean, then carry out thin pass, the roller spacing is 0.3mm, make triangle packs, thin pass 7 times, adjust the roller spacing to 2-3mm, roll 2-4 times to take off the sheet, and place it at room temperature for 12h to obtain the mixed rubber; finally, vulcanize it at a vulcanization temperature of 160°C, a time of 15min, and a pressure of 15MPa to obtain a rubber composite material.

[0058] Comparative Example 5

[0059] Compared with Example 1, the silicon dioxide modified by the silane coupling agent and the graphene oxide modified by the tannic acid are not composited.

[0060] Step 1: Dissolve 3g Si69 in 100ml ethanol-water (1:1) solution and fully hydrolyze it, then add 20g SiO2, stir magnetically at 25℃ for 3h, so that the silanol produced by the hydrolysis of Si69 reacts with the hydroxyl groups on the surface of SiO2 to undergo a dehydration reaction and is grafted onto the surface of SiO2, centrifuge several times (10000rpm, 2min) to wash and remove the ungrafted Si69, dry in an oven at 60℃ for 48h, and set aside;

[0061] Step 2: Add 4gTA to 100ml deionized water, stir magnetically for 30min, then add 1gGO and ultrasonicate for 30min, then react the mixed solution at 90℃ for 8h to obtain TA-rGO suspension. After the reaction is completed, centrifuge and wash several times to remove excess TA. The centrifugal speed is 10000rpm, and the centrifugation is performed for 10min. The upper liquid is removed, the precipitate is washed with deionized water, and dried to obtain TA-rGO.

[0062] Step 3: Set the speed of the internal mixer to 80rpm and the temperature to 60℃; add 100 parts of nitrile rubber into the internal mixer and plasticize for 1 minute, then add 50 parts of N550 carbon black and continue to mix for 1 minute, then add 5 parts of nano zinc oxide, 0.5 parts of accelerator DM, and 2 parts of antioxidant 4010NA and continue to mix for 2 minutes, then add the above-mentioned 2.94 parts of SiO2 and 0.06 parts of TA-rGO composite filler and continue to mix for 2 minutes, then add 2 parts of softener stearic acid and continue to mix for 2 minutes; clean for 1 minute, and debind at 140℃, and dry in an oven at 140℃ for 30 minutes after debinding to obtain the mixed rubber.

[0063] Step 4: Move the rubber material of step 4 to an open mixing mill for mixing, set the temperature of the front roller to 50°C, and the temperature of the rear roller to 55°C; add 1 part of sulfur and 0.3 parts of the remaining accelerator back and forth in several times to mix, sweep the wheel plate, cut the left and right kneading knife 5 times after it is clean, then carry out thin pass, the roller spacing is 0.3mm, make triangle bag, thin pass 7 times, adjust the roller spacing to 3mm, roll 4 times to take off the sheet, and place it at room temperature for 12h to obtain the mixed rubber; finally, vulcanize it at a vulcanization temperature of 160°C, a time of 15min, and a pressure of 15MPa to obtain a rubber composite material.

[0064] Example 2

[0065] A rubber composite material, the preparation method of which is as follows:

[0066] Step 1: Dissolve 3g Si69 in 100ml ethanol-water (1:1) solution and fully hydrolyze it, then add 20g SiO2, stir magnetically at 25℃ for 3h, so that the silanol produced by the hydrolysis of Si69 reacts with the hydroxyl groups on the surface of SiO2 to undergo a dehydration reaction and is grafted onto the surface of SiO2, centrifuge several times (10000rpm, 2min) to wash and remove the ungrafted Si69, dry in an oven at 60℃ for 48h, and set aside;

[0067] Step 2: Add 4gTA to 100ml deionized water, stir magnetically for 30min, then add 1gGO and ultrasonicate for 30min, then react the mixed solution at 90℃ for 8h to obtain TA-rGO suspension. After the reaction is completed, centrifuge and wash several times to remove excess TA. The centrifugal speed is 10000rpm, and the centrifugation is performed for 10min. The upper liquid is removed and the precipitate is washed with deionized water.

[0068] Step 3: Preparation of TA-rGO / SiO2 composite filler: Take 0.4g of TA-rGO and add it into 100ml of deionized water, mix it evenly by ultrasonic for 30min to form a suspension, add the modified SiO2 obtained in step 1 (mass ratio GO:SiO2=1:40) into the suspension, stir it magnetically at 25℃ for 4h, put it into an oven and dry it at 60℃ for 48h to obtain TA-rGO / SiO2 composite filler.

[0069] Step 4: Set the speed of the internal mixer to 80rpm and the temperature to 60℃; add 100 parts of nitrile rubber into the internal mixer and plasticize for 1 minute, then add 50 parts of N550 carbon black and continue to mix for 1 minute, then add 5 parts of nano zinc oxide, 0.5 parts of accelerator DM, and 2 parts of antioxidant 4010NA and continue to mix for 2 minutes, then add the above 3 parts of TA-rGO / SiO2 composite filler and continue to mix for 2 minutes, then add 2 parts of softener stearic acid and continue to mix for 2 minutes; clean for 1 minute, and debind at 140℃, and dry in an oven at 140℃ for 30 minutes after debinding to obtain the mixed rubber.

[0070] Step 5: Move the rubber material of step 4 to an open mixing mill for mixing, set the temperature of the front roller to 50°C, and the temperature of the rear roller to 55°C; add 1 part of sulfur and 0.3 parts of the remaining accelerator back and forth in several times to mix, sweep the wheel plate, cut the left and right kneading knife 5 times after it is clean, then carry out thin pass, the roller spacing is 0.3mm, make triangle bag, thin pass 7 times, adjust the roller spacing to 3mm, roll 4 times to take off the sheet, and place it at room temperature for 12h to obtain the mixed rubber; finally, vulcanize it at a vulcanization temperature of 160°C, a time of 15min, and a pressure of 15MPa to obtain a rubber composite material.

[0071] Example 3

[0072] A rubber composite material, the preparation method of which is as follows:

[0073] Step 1: Dissolve 3g Si69 in 100ml ethanol-water (1:1) solution and fully hydrolyze it, then add 20g SiO2, stir magnetically at 25℃ for 3h, so that the silanol produced by the hydrolysis of Si69 reacts with the hydroxyl groups on the surface of SiO2 to undergo a dehydration reaction and is grafted onto the surface of SiO2, centrifuge several times (10000rpm, 2min) to wash and remove the ungrafted Si69, dry in an oven at 60℃ for 48h, and set aside;

[0074] Step 2: Add 4gTA to 100ml deionized water, stir magnetically for 30min, then add 1gGO and ultrasonicate for 30min, then react the mixed solution at 90℃ for 8h to obtain TA-rGO suspension. After the reaction is completed, centrifuge and wash several times to remove excess TA. The centrifugal speed is 10000rpm, and the centrifugation is performed for 10min. The upper liquid is removed and the precipitate is washed with deionized water.

[0075] Step 3: Preparation of TA-rGO / SiO2 composite filler: Take 0.4g of TA-rGO and add it into 100ml of deionized water, mix it evenly by ultrasonic for 30min to form a suspension, add the modified SiO2 obtained in step 1 (mass ratio GO:SiO2=1:60) into the suspension, stir it magnetically at 25℃ for 4h, put it into an oven and dry it at 60℃ for 48h to obtain TA-rGO / SiO2 composite filler.

[0076] Step 4: Set the speed of the internal mixer to 80rpm and the temperature to 60℃; add 100 parts of nitrile rubber into the internal mixer and plasticize for 1 minute, then add 50 parts of N550 carbon black and continue to mix for 1 minute, then add 5 parts of nano zinc oxide, 0.5 parts of accelerator DM, and 2 parts of antioxidant 4010NA and continue to mix for 2 minutes, then add the above 3 parts of TA-rGO / SiO2 composite filler and continue to mix for 2 minutes, then add 2 parts of softener stearic acid and continue to mix for 2 minutes; clean for 1 minute, and debind at 140℃, and dry in an oven at 140℃ for 30 minutes after debinding to obtain the mixed rubber.

[0077] Step 5: Move the rubber material of step 4 to an open mixing mill for mixing, set the temperature of the front roller to 50°C, and the temperature of the rear roller to 55°C; add 1 part of sulfur and 0.3 parts of the remaining accelerator back and forth in several times to mix, sweep the wheel plate, cut the left and right kneading knife 5 times after it is clean, then carry out thin pass, the roller spacing is 0.3mm, make triangle bag, thin pass 7 times, adjust the roller spacing to 3mm, roll 4 times to take off the sheet, and place it at room temperature for 12h to obtain the mixed rubber; finally, vulcanize it at a vulcanization temperature of 160°C, a time of 15min, and a pressure of 15MPa to obtain a rubber composite material.

[0078] Example 4

[0079] A rubber composite material, the preparation method of which is as follows:

[0080] Step 1: Dissolve 3g Si69 in 150ml ethanol-water (1:1) solution and fully hydrolyze it, then add 15g SiO2, stir magnetically at 30℃ for 4h, so that the silanol produced by the hydrolysis of Si69 reacts with the hydroxyl groups on the surface of SiO2 to undergo a dehydration reaction and is grafted onto the surface of SiO2, centrifuge several times (10000rpm, 2min) to wash and remove the ungrafted Si69, dry in an oven at 60℃ for 48h, and set aside;

[0081] Step 2: Add 6gTA to 70ml deionized water, stir magnetically for 30min, then add 1gGO and ultrasonicate for 30min, then react the mixed solution at 90℃ for 10h to obtain TA-rGO suspension. After the reaction is completed, centrifuge and wash several times to remove excess TA. The centrifugal speed is 10000rpm, centrifuge for 10min, remove the upper liquid, and wash the precipitate with deionized water.

[0082] Step 3: Preparation of TA-rGO / SiO2 composite filler: Take 0.4g of TA-rGO and add it into 150ml of deionized water, mix evenly by ultrasonication for 30min to form a suspension, add the modified SiO2 obtained in step 1 (mass ratio GO:SiO2=1:50) into the suspension, stir magnetically at 25℃ for 4h, put it into an oven and dry it at 60℃ for 48h to obtain TA-rGO / SiO2 composite filler.

[0083] Step 4: Set the speed of the internal mixer to 80rpm and the temperature to 60℃; add 100 parts of nitrile rubber into the internal mixer and plasticize for 1 minute, then add 80 parts of N550 carbon black and continue to mix for 1 minute, then add 6 parts of nano zinc oxide, 1 part of accelerator DM, and 5 parts of antioxidant 4010NA and continue to mix for 2 minutes, then add the above 6 parts of TA-rGO / SiO2 composite filler and continue to mix for 2 minutes, then add 2.5 parts of softener stearic acid and continue to mix for 2 minutes; clean for 1 minute, and debind at 140℃, and dry in an oven at 140℃ for 30 minutes after debinding to obtain the mixed rubber.

[0084] Step 5: Move the rubber material of step 4 to an open mill for mixing, set the temperature of the front roller to 50°C, and the temperature of the rear roller to 55°C; add 1.5 parts of sulfur and 0.5 parts of the remaining accelerator back and forth in several times to mix, sweep the wheel plate, cut the left and right kneading knife 5 times after it is clean, then carry out thin pass, the roller spacing is 0.3mm, make a triangle bag, thin pass 7 times, adjust the roller spacing to 3mm, roll 4 times to take off the sheet, and place it at room temperature for 12 hours to obtain the mixed rubber; finally, vulcanize it at a vulcanization temperature of 160°C, a time of 15min, and a pressure of 15MPa to obtain a rubber composite material.

[0085] Example 5

[0086] A rubber composite material, the preparation method of which is as follows:

[0087] Step 1: Dissolve 3g Si69 in 250ml ethanol-water (1:1) solution and fully hydrolyze it, then add 30g SiO2, stir magnetically at 30℃ for 4h, so that the silanol produced by the hydrolysis of Si69 reacts with the hydroxyl groups on the surface of SiO2 to undergo a dehydration reaction and is grafted onto the surface of SiO2, centrifuge several times (10000rpm, 2min) to wash and remove the ungrafted Si69, dry in an oven at 60℃ for 48h, and set aside;

[0088] Step 2: Add 5gTA to 50ml deionized water, stir magnetically for 30min, then add 1gGO and ultrasonicate for 30min, then react the mixed solution at 70°C for 12h to obtain TA-rGO suspension. After the reaction is completed, centrifuge and wash several times to remove excess TA. The centrifugal speed is 10000rpm, centrifuge for 10min, remove the upper liquid, and wash the precipitate with deionized water.

[0089] Step 3: Preparation of TA-rGO / SiO2 composite filler: Take 0.4g of TA-rGO and add it into 200ml of deionized water, mix it evenly by ultrasonic for 30min to form a suspension, add the modified SiO2 obtained in step 1 (mass ratio GO:SiO2=1:50) into the suspension, stir it magnetically at 25℃ for 4h, put it into an oven and dry it at 60℃ for 48h to obtain TA-rGO / SiO2 composite filler.

[0090] Step 4: Set the speed of the internal mixer to 80rpm and the temperature to 60℃; add 100 parts of nitrile rubber into the internal mixer and plasticize for 1 minute, then add 60 parts of N550 carbon black and continue to mix for 1 minute, then add 4 parts of nano zinc oxide, 0.5 parts of accelerator DM, and 2 parts of antioxidant 4010NA and continue to mix for 2 minutes, then add the above 5 parts of TA-rGO / SiO2 composite filler and continue to mix for 2 minutes, then add 3 parts of softener stearic acid and continue to mix for 2 minutes; clean for 1 minute, and debind at 140℃, and dry in an oven at 140℃ for 30 minutes after debinding to obtain the mixed rubber.

[0091] Step 5: Move the rubber material of step 4 to an open mill for mixing, set the temperature of the front roller to 50°C, and the temperature of the rear roller to 55°C; add 2 parts of sulfur and 0.5 parts of the remaining accelerator back and forth in several times to mix, sweep the wheel plate, cut the left and right kneading knife 5 times after it is clean, then carry out thin pass, the roller spacing is 0.2-0.5mm, make triangle packages, thin pass 7 times, adjust the roller spacing to 3mm, roll 4 times to take off the sheet, and place it at room temperature for 12 hours to obtain the mixed rubber; finally, vulcanize it at a vulcanization temperature of 160°C, a time of 15min, and a pressure of 15MPa to obtain a rubber composite material.

[0092] Table 1

[0093] Tensile strength(MPa) Tear strength (N / mm) <![CDATA[DIN wear (mm 3 )]]> Example 1 13.7 33.4 171.8 Example 2 13.1 32.5 178.1 Example 3 12.6 31.2 185.3 Comparative Example 1 10.3 23.5 263.1 Comparative Example 2 11.6 27.4 210.6 Comparative Example 3 12.1 29.7 196.8 Comparative Example 4 12.1 31.5 179.6 Comparative Example 5 12.4 30.9 177.5

[0094] It can be seen from Table 1 that the rubber performance is best when only 3 parts of MSTA-rGO composite filler are added, and the tensile strength, tear strength and wear resistance are increased by 29.2%, 42.1% and 34.7% respectively. That is, adding a small amount of the prepared composite material can significantly improve the strength and wear resistance of the rubber.

[0095] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principle of the present invention should be included in the protection scope of the present invention.

Claims

1. A method for preparing a modified TA-rGO / SiO2 composite filler, characterized in that: The following steps are involved: Step 1: dispersing and dissolving the silane coupling agent and SiO2 in solvent I to carry out a grafting reaction to obtain silane coupling agent-modified SiO2; Step 2: Disperse and dissolve TA and GO in solvent II for reduction reaction to obtain TA-rGO; Step 3: Disperse the silane coupling agent modified SiO2 and TA-rGO in solvent III and stir evenly, and evaporate to dryness to obtain TA-rGO / SiO2 composite filler.

2. The method for preparing the modified TA-rGO / SiO2 composite filler according to claim 1, characterized in that: The silane coupling agent is 3-aminopropyltriethoxysilane, 3-(methacryloyloxy)propyltrimethoxysilane or bis-[γ-(triethoxysilyl)propyl]tetrasulfide.

3. The method for preparing the modified TA-rGO / SiO2 composite filler according to claim 1, characterized in that: The mass ratio of the silane coupling agent to SiO2 is 1:(5-10), and the mass volume ratio of SiO2 to solvent I is 1:(5-10) g / ml; the temperature of the grafting reaction is 25-30°C, and the time is 3-4h.

4. The method for preparing the modified TA-rGO / SiO2 composite filler according to claim 1, characterized in that: The solvent I is water and / or ethanol; the solvent II is water; and the solvent III is water.

5. The method for preparing the modified TA-rGO / SiO2 composite filler according to claim 1, characterized in that: The mass ratio of TA to GO is (4-6):1, and the mass volume ratio of GO to solvent II is (10-20):1 mg / ml.

6. The method for preparing the modified TA-rGO / SiO2 composite filler according to claim 1, characterized in that: The temperature of the reduction reaction is 70-90° C. and the time is 8-12 hours.

7. The method for preparing the modified TA-rGO / SiO2 composite filler according to claim 1, characterized in that: The mass ratio of the TA-rGO and the silane coupling agent modified SiO2 is 1: (40-60), and the mass volume ratio of the silane coupling agent modified SiO2 and the solvent III is 1: (5-10) g / ml.

8. The modified TA-rGO / SiO2 composite filler prepared by the method according to any one of claims 1 to 7.

9. A rubber composite material, characterized in that: The composition comprises, by weight: 100 parts of nitrile rubber, 50-80 parts of carbon black, 3-6 parts of modified TA-rGO / SiO2 composite filler, 1-2 parts of vulcanizer, 0.8-1.5 parts of accelerator, 4-6 parts of nano zinc oxide, 2-3 parts of stearic acid and 2-5 parts of antioxidant.

10. The rubber composite material according to claim 9, characterized in that: The vulcanizing agent is sulfur; the accelerator is accelerator DM; and the antioxidant is antioxidant 4010NA.

Citation Information

Patent Citations

  • Electrostatic assembly graphene oxide / silicon dioxide natural rubber composite material and preparation

    CN115181341A